PENGARUH RETURN ON EQUITY, LEVERAGE, DAN KEBIJAKAN DIVIDEN TERHADAP ABNORMAL RETURN - Firda Safiroh; Mu'minatus Sholichah (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This study aims to determine the effect of Return on Equity, leverage, and dividend policy on abnormal return. This type of research is quantitative research using secondary data. Methods of collecting data from this study using the method of documentation. The sample in this study is companies listed on the Indonesia Stock Exchange and LQ45 indexed in 2019-2021. The sample was selected by purposive sampling method and obtanined 28 samples. The test is carried out using multiple linear regression using SPSS 24. The results of this research show that Return on Equity, and leverage has no significant effect on abnormal return. Dividend policy has a significant effect on abnormal return. This study has limited research variabels and research years.